The Relationship of the Transformative Learning Experience on Substance Abuse Treatment Outcomes: The Hudson Lake Recovery Camp Curriculum - Melodie Fair (Adult Education Research Conference, 2006)
This paper reports preliminary results of a qualitative study. It appears that clients who successfully completed the Hudson Lake Recovery Camp substance abuse treatment program reported that positive transformative learning experiences helped facilitate their recovery process.
Keywords: Qualitative research; Alaska native education; recovery